IMPLIKASI DAN TANTANGAN PEMBENTUKAN KOMUNITAS EKONOMI ASEAN TERHADAP PEREKONOMIAN NASIONAL - Firdausy, Carunia Mulya (Jurnal Ekonomi, 2010)
ASEAN Â Economic Community (AEC) has been agreed by the ASEAN leaders in 2003 as one mechanism to increase the social economic welfare of the people in ASEAN countries. Whilst it is no doubt the formation of AEC will give many benefits to ASEAN countries, there will be also negative impacts of the AEC. This paper aimed at analysing the implication and challenges of the formation of the ASEAN Economic Community (AEC) toward Indonesian economy with particular attention to agricultural sector and the micro and small-medium enterprises (SMEs) development. The paper argues inter alia that the formation of AEC Â will give benefit to ASEAN countries if and only if the ASEAN community has one voice in socio-economic and policial commitment and coordination. The economic sectors that need further greater improvement toward the success of the formation are agricultural sector and the micro, small and medium enterprises. Thus, much remain to be done by ASEAN countries in general and in Indonesia in particular toward the success of .the formation of AEC.